Automatic implantable defibrillator discharge resulting from routine pacemaker programming. - Gottlieb C; Miller JM; Rosenthal ME; Marchlinski FE (Pacing & Clinical Electrophysiology, 1988)
A middle-aged gentleman with an idiopathic dilated cardiomyopathy, drug-refractory sustained ventricular arrhythmia, and high-degree AV block was managed with an automatic implantable cardioverter-defibrillator (AICD) and a Cordis Multicor II VVI pacemaker. During a routine follow-up visit, the pacemaker threshold was determined. Seven seconds after reprogramming the Cordis pacemaker to the 'star' VVI mode, the AICD discharged. The time to discharge after reprogramming the pacemaker equalled the previously determined AICD charge time. No other rhythm disturbance was documented and the rate with double counting of pacemaker stimulus and QRS complex was less than the triggering rate for the AICD. In conclusion, the AICD can be triggered by pacemaker programming signals unrelated to subsequent pacemaker function.